Features of biology and morphology of common fox Vulpes vulpes L. (1758) in the Kharkiv Region - Токарський, В. А.; Грубник, В. В.; Токарська, Н. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The dynamics of number of common fox in the territory of the Kharkiv region and factors influencing it have been analyzed. In recent years, there has been an increase in the number, which may indicate that hunting in this territory has no decisive influence on the population state. Morphometric data and cranial indices of foxes have been obtained. In more than 50% of the individuals morphometric parameters are stable, in the both sexes. Of the 28 craniometric parameters the width of supraorbital processes in females is the most variable (Cv=10,54); highly variable are the width of choanae and the width of the upper canine tooth at the base; the width of the rostrum and the length of nasal bones, the width of the auditory capsule and the length of the brain department. Variability of 19 skull characteristics in males is higher than that of females. Less variable are the width of the brain capsule (both in males and females), the length of the upper carnassial and the width between auditory foramens (in males). The differences between craniometric parameters of males and females are valid for 6 parameters (p˂0.05). The sample is largely corresponds to the data of L.S.Shevchenko (1987) in the steppe zone, which is consistent with zoning of the Kharkiv region. Winter feeding habits have been analyzed: feed of the main group includes: mouse-like rodents, marmots, birds and plant food (fruits and seeds). Materials on the infestation of foxes of the north-east of Ukraine have been presented. In the trapped animals there have been found parasites: Toxocara spp. (Ascaridida, Nematoda) – 14 adults, in the intestine of 10 males and 4 females; 3 adult individuals in the stomach of 2 females and 1 male. Moreover, the foxes obtained in Velikiy Burluk District in 2013–2015 were infected by fleas: badger, Paraceras melis (male), and fox, Chaetopsylla globiceps (2 females).